2004
DOI: 10.1557/jmr.2004.0278
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropies in the electrical properties of rod-like aggregates of liquid crystalline phthalocyanines: Direct current conductivities and field-effect mobilities

Abstract: The direct current (dc) conductivities and organic field-effect transistor (OFET) characteristics of a class of octa-substituted liquid crystalline (discotic mesophase) phthalocyanines (Pcs) are discussed. These molecules self-organize into columnar aggregates with large coherence lengths (up to approximately 300 nm). Langmuir–Blodgett films of these molecules were horizontally transferred to either interdigitated microelectrodes (IME) or OFET substrates, so that current flow could be measured either parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 53 publications
(94 reference statements)
1
44
0
Order By: Relevance
“…For example, the self-assembly of an amphiphilic hexa-perihexabenzocoronene gave rise to a redoxactive graphitic nanotube that consisted of helical arrays of p-stacked molecules and, upon oxidation, showed electrical conductivity. [5] Liquid-crystalline discotic materials, such as side-chain-modified phthalocyanines [6] and porphyrins, as well as triphenylenes, [7] self-organize into columnar aggregates and have become of interest as potential solutionprocessed molecular electronic materials. [8] In general, columnar discotic liquid crystals consist of a rigid central core-which can be planar, pyramidal, conical or have another similar geometry-surrounded by a number of flexible groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the self-assembly of an amphiphilic hexa-perihexabenzocoronene gave rise to a redoxactive graphitic nanotube that consisted of helical arrays of p-stacked molecules and, upon oxidation, showed electrical conductivity. [5] Liquid-crystalline discotic materials, such as side-chain-modified phthalocyanines [6] and porphyrins, as well as triphenylenes, [7] self-organize into columnar aggregates and have become of interest as potential solutionprocessed molecular electronic materials. [8] In general, columnar discotic liquid crystals consist of a rigid central core-which can be planar, pyramidal, conical or have another similar geometry-surrounded by a number of flexible groups.…”
Section: Introductionmentioning
confidence: 99%
“…The phase transition between the columnar mesophase and the new phase is clearly visible. In both phases, two relaxation processes are evident, one at around 10 6 Hz and the other at around 10 3 Hz. Both relaxations disappear upon solidification and they are thermally activated.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, the effort of many scientists working on enhancement of the electric properties of phthalocya nine films and the efficiency of their production has been directed toward synthesis of octa substituted amphiphilic derivatives [331][332][333][334][335][336][337][338]. It was shown that such compounds can form true monolayers consisting of stacking aggregates and existing upon compression up to pressures of no more than 10-15 mN/m.…”
Section: Electric Conductivity and Magnetic Properties Of Lbfmentioning
confidence: 99%
“…The conductivity of such films of amphiphilic phthalocyanines lies in the range of 10 -9 -10 -8 S/m -1 and can be increased by two to three orders of magni tude by electrochemical doping [337,338].…”
Section: Electric Conductivity and Magnetic Properties Of Lbfmentioning
confidence: 99%